2022
DOI: 10.3390/plants11131656
|View full text |Cite
|
Sign up to set email alerts
|

Improving Peach Fruit Quality Traits Using Deficit Irrigation Strategies in Southern Tunisia Arid Area

Abstract: The peach (Prunus persica L.) is one of Tunisia’s major commercial fruit crops and is considered one of the biggest water consumers of all crops. In warm and arid areas of southern Tunisia, irrigation is necessary to ensure orchard longevity and high yield and fruit quality. Nevertheless, under water-scarcity conditions and low water quality, water management should rely on efficient deficit irrigation strategies. In this study, sustained deficit irrigation (DI) and partial root-zone drying (PRD50) at 50% of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Several deficit irrigation strategies have been developed (e.g., regulated deficit irrigation (RDI), sustained deficit irrigation (SDI), or partial root zone drying (PRD), among others), and have shown beneficial impacts both on water saving as well as on WP improvement in arid and semi-arid areas [14][15][16]. The slight yield losses due deficit irrigation were compensated by an improvement in fruit quality for many fruit species, such as Prunus persica [17,18], Malus domestica [19], Vitis vinifera [20], and Prunus domestica [21]. A drip irrigation system is used when applying deficit irrigation and allows for precise control of the water amount applied, especially in the PRD strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Several deficit irrigation strategies have been developed (e.g., regulated deficit irrigation (RDI), sustained deficit irrigation (SDI), or partial root zone drying (PRD), among others), and have shown beneficial impacts both on water saving as well as on WP improvement in arid and semi-arid areas [14][15][16]. The slight yield losses due deficit irrigation were compensated by an improvement in fruit quality for many fruit species, such as Prunus persica [17,18], Malus domestica [19], Vitis vinifera [20], and Prunus domestica [21]. A drip irrigation system is used when applying deficit irrigation and allows for precise control of the water amount applied, especially in the PRD strategy.…”
Section: Introductionmentioning
confidence: 99%
“…As a fresh food fruit, the Chinese olive has rich nutritional value. Studies have shown that it is rich in vitamins and can contain 10 times higher vitamin C (VC) than apple and 5 times higher than pear and peach ( Toumi et al, 2022 ). It is rich in the trace element selenium, also known as the “life element” helping the organism retard aging processes ( Mojadadi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…"In context of plant biomass production, yield and quality of tomato under deficit irrigation, showed mixed results. Field trials under drought stress either resulted a drastic reduction in dry mass production, or no adverse impacts on yield and quality of fruits" [21][22][23]. "However stress affected yield of tomato when occurred throughout the reproductive stage and development period, but quality during the final or ripening stage" [24].…”
Section: Introductionmentioning
confidence: 99%